Association between respiratory diseases and molar-incisor hypomineralization: A systematic review and meta-analysis - Né, Yago Gecy de Sousa; Frazão, Deborah Ribeiro; Lopes, Géssica de Oliveira; Fagundes, Nathália Carolina Fernandes; Souza-Rodrigues, Renata Duarte; Paula-Silva, Francisco Wanderley Garcia; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Medicine, 2022)
MIH (molar-incisor hypomineralization) is a qualitative enamel developing abnormality involving the occlusal and/or incisal third of one or more molars or permanent incisors, caused by systemic factors. Several systemic disorders and environmental factors, such as respiratory diseases, have been reported as probable causes of MIH. Thus, this work aimed to evaluate whether respiratory diseases and MIH are associated. The searches were carried out in electronic databases, including PubMed, Scopus, Web of Science, the Cochrane Library, LILACS, OpenGrey, and Google Scholar. The acronym PECO was used, in which the P (population) was humans in permanent dentition stage; (E - exposure) molar-incisor hypomineralization; (C - comparison) reference population and (O - outcome) respiratory diseases. After the search retrieval, the duplicates were removed, and the articles were evaluated by title and abstract; then, the papers were read and thoroughly assessed. After selection, the risk of bias assessment was performed using the Newcastle-Ottawa Scale (NOS) for observational studies. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) tool was used to assess the level of evidence. 3,666 were found through the searches. After exclusion by duplicates, title, abstract, and full-reading, 13 articles remained. The articles included in this review evaluated the association of MIH with asthma, tonsilitis, pneumonia, and bronchitis. Most reports showed a low risk of bias. When exploring through GRADE, a very low level of evidence was found. We observed that the included studies showed that children with MIH had more respiratory diseases than the group that did not have MIH.